2021
DOI: 10.1371/journal.pone.0259286
|View full text |Cite
|
Sign up to set email alerts
|

Gender-wise comparison of oral health quality of life and its relationship with oral health parameters among elderly from Wroclaw, south-west Poland

Abstract: Background In recent years, there has been an increase of aging population with longer life expectancy in females. This study aims to compare some oral health parameters and quality of life in the elderly. Methods The survey involved 500 urban residents (Wroclaw, Poland) aged 65 and older, of both gender. Socio-demografic data were assessed by self-reported questionnaire. Clinical examination included oral health assessment by the World Health Organization criteria with extension and oral dryness (Chalacombe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Sex-related significant difference in patients was found only in the dimension of Psychosocial Impacts ; women were more likely to report oral illness of a psychosocial nature than men. This finding is in accordance with conclusions reported by several other authors [ 23 , 44 , 45 ]. Difference in the perception of psychosocial impacts of OHRQoL on daily activities between the sexes may be caused by individual and subjective concepts related to beauty and aesthetic standards, imposed by the social demands and personal needs [ 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…Sex-related significant difference in patients was found only in the dimension of Psychosocial Impacts ; women were more likely to report oral illness of a psychosocial nature than men. This finding is in accordance with conclusions reported by several other authors [ 23 , 44 , 45 ]. Difference in the perception of psychosocial impacts of OHRQoL on daily activities between the sexes may be caused by individual and subjective concepts related to beauty and aesthetic standards, imposed by the social demands and personal needs [ 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…We speculate that the higher prevalence of activity limitations due to dental or oral problems in women than in men may be associated with the tendency of men to ignore oral health more often than women do [31]. A previous study reported no significant differences between men and women in oral health parameters among older adults, which is consistent with the results of our study [32]. Older women reported more back or neck problems as the reasons for activity limitations compared to men.…”
Section: Discussionsupporting
confidence: 91%
“…In a cross-sectional study of Turkish dental patients using the OHIP-14 scale, it was found that the OHRQoL of male dental patients was higher than that of female patients [ 19 ]. In a study investigating the gender comparison of OHRQoL and its relationship with oral health parameters in the elderly in Wroclaw, southwestern Poland, no gender differences in oral health parameters were found [ 20 ]. Considering the contradictory results, there was a need to determine the invariance of the measurement of the OHIP-14 in males and females and to determine whether the differences between the groups shown by the study results were actual differences or due to measurements.…”
Section: Introductionmentioning
confidence: 99%